De la portée politique des œuvres d’art. Bourdieu sur le chemin de Francfort - Federico Tarragoni (Association Internationale des Sociologues de Langue Française, 2021)
It is often thought that the two critical sociologies of art, that of Pierre Bourdieu and that of the Frankfurt School, are unrelated (due to the effective absence of quotations of the critical theory on the part of Pierre Bourdieu). However, there are important affinities in the way in which Pierre Bourdieu thinks the conflictive potential of artistic creation: if the myth of the "uncreated creator" is overcome, and if, as in the cases of Gustave Flaubert or Édouard Manet, the artistic creation deconstructs the principles of vision and division of the social world, it takes on political meanings. This proposal finds important echoes in Frankfurt School, between the critique of the illusion of the "bourgeois genius", as in Max Horkheimer and Theodor W. Adorno’s review of the myth of Ulysses and the sirens, and the hopes placed in Arnold Schönberg's musical revolution.